The relationship of perivascular adipose tissue and atherosclerosis in the aorta and carotid arteries, determined by magnetic resonance imaging. (July 2018) - Alkhalil, Mohammad; Edmond, Evan; Edgar, Laurienne; Digby, Janet E; Omar, Omar; Robson, Matthew D; Choudhury, Robin P
Background and aims: Imaging studies have relied on the 'overall' volumetric quantification of perivascular adipose tissue. We sought to assess the relationship of circumferential distribution between perivascular adipose tissue and adjacent wall thickness of carotid and aortic arteries using dedicated magnetic resonance imaging sequences. Methods: Vessel wall and perivascular adipose tissue were acquired using magnetic resonance imaging (1.5 T). Co-registered images were segmented separately, and measurements of both perivascular adipose tissue and vessel wall were obtained along radii of the vessel spaced at angles of 5° each. Results: In total, 29 patients were recruited. Perivascular adipose tissue thickness of the aorta was 3.34 ± 0.79 mm with specific pattern of 'double peaks' distribution, while carotid perivascular adipose tissue had no identifiable pattern with thickness of 0.8 ± 0.91 mm. Although statistically significant, the correlation between perivascular adipose tissue thickness and wall thickness in carotid arteries with normal (r = 0.040, p = 0.001) or with abnormal wall thickness (r = –0.039, p = 0.015) was merely nominal. Similarly, perivascular adipose tissue of the aorta had very weak correlation with normal aortic wall thickness (r = 0.010, p = 0.008) but not with the abnormal ones (r = −0.05, p = 0.29). Conclusion: Dissociation between the spatial distribution of perivascular adipose tissue and arterial wall thickening in the aorta and carotid arteries does not support that perivascular adipose tissue has a causal role in promoting atherosclerotic plaque via a paracrine route. Yet, perivascular adipose tissue functional properties were not examined in this study.